Characterization of an Intraplate Seismogenic Zone Using Geophysical and Borehole Data: The Vila Franca de Xira Fault, Portugal - Carvalho, João (2021)
ABSTRACT: The Vila Franca de Xira (VFX) fault is a regional fault zone located about 25 km northeast of Lisbon, affecting Neogene sediments. Recent shear-wave seismic studies show that this complex fault zone is buried beneath Holocene sediments and is deforming the alluvial cover, in agreement with a previous work that proposes the fault as the source of the 1531 Lower Tagus Valley earthquake. In this work, we corroborate these results using S-wave, P-wave, geoelectric, ground-penetrating radar and borehole data, confirming that the sediments deformed by several fault branches are of Upper Pleistocene to Holocene. Accumulated fault vertical offsets of about 3 m are estimated from the integrated interpretation of geophysical and borehole data, including 2D elastic seismic modeling, with an estimated resolution of about 0.5 m. The deformations affecting the Tagus alluvial sediments probably resulted from surface or near-surface rupture of the VFX fault during M similar to 7 earthquakes, reinforcing the fault as the seismogenic source of regional historical events, as in 1531, and highlighting the need for preparedness for the next event.